Prevalence of Subclinical Coccidiosis in Broilers - Prajapati, Ramdatt K; Ghodasara, Dinesh J; Bhanderi, Bharat B; Gehani, Mukesh T (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was carried out to assess the prevalence of subclinical coccidiosis in broilers affected with different diseases/ pathological conditions received for post-mortem examination. The study was carried out in 50 broiler flocks of 2-7 weeks age. The study comprised of molecular detection and oocyst count (OPG) of subclinical coccidiosis. Samples were collected from three birds in each flock and observed by direct microscopic method. Out of 50 flocks investigated, Eimeria oocysts were detected in 17 (34%) broiler flocks by direct smear examination. On molecular detection of Eimeria species in 50 flocks, 19 (38%) were found positive in which E. tenella and E. acervulina were detected. Among the 50 flocks tested Eimeria species encountered were E. tenella and E. acervulina in 30% and 8%, respectively.